(untitled) (Foro de Educacion, 2019)
Framed in research in co-labor (Ballena & Unamuno, 2017b; Leiva, 2011; Lassiter, 2005; Rappaport, 2008), this study focuses on the analysis of ethnographic registers carried out in the framework of wichi children book «N’ku Ifweln’uhu» (My mother taught me) production. First, I problematize research in indigenous context in Argentina, especially in relation to the place of indigenous people in the research processes. Then, I present the context where we work to contextualize production of the aforementioned children book. The use of ethnography to recover the traditional knowledge of wichi mothers and the dialogue with Western school knowledge is discussed here. The result of the analysis of these registers will allow me, finally, to propose some conclusions about sociolinguistic ethnography as space and practice collective knowledge production in the field of multilingual education.